2005
DOI: 10.1002/ceat.200500093
|View full text |Cite
|
Sign up to set email alerts
|

CFD Prediction of Flow and Homogenization in a Stirred Vessel: Part II Vessel with Three and Four Impellers

Abstract: This article deals with CFD simulations of flow inside stirred vessels equipped with three and four radial or axial impellers mounted on the same shaft. A comparison was made between simulated data and experiments for one-and two-impeller systems and was presented in Part I [1]. The effect of the lowest impeller off-bottom clearance, number of impellers used, and impeller type on the tracer distribution was studied. The simulations were mainly focused on the grid size and type and the analysis of the concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Montante et al required a strongly lower turbulent Schmidt number, Sc t = 0.1 (Montante et al, 2005), to yield agreement with experiments in a 4 impeller tank; similar observations were made in other studies (Delafosse et al, 2014;. Moštěk et al (2005) did not tune Sc t , and reported an approximately 20% overestimation in  95 compared to their measurements with 3 impellers (40% compared to Jahoda and Machon (1994)). They found decent agreement in 4 impeller systems compared to their own measurements (they did over-estimate  95 compared to Jahoda and Machon (1994)).…”
Section: Multi-impeller Systemssupporting
confidence: 56%
See 1 more Smart Citation
“…Montante et al required a strongly lower turbulent Schmidt number, Sc t = 0.1 (Montante et al, 2005), to yield agreement with experiments in a 4 impeller tank; similar observations were made in other studies (Delafosse et al, 2014;. Moštěk et al (2005) did not tune Sc t , and reported an approximately 20% overestimation in  95 compared to their measurements with 3 impellers (40% compared to Jahoda and Machon (1994)). They found decent agreement in 4 impeller systems compared to their own measurements (they did over-estimate  95 compared to Jahoda and Machon (1994)).…”
Section: Multi-impeller Systemssupporting
confidence: 56%
“…This requires that CFD simulations sufficiently capture the true mixing behavior, which gave rise to a significant body of validation literature. A review of literature focusing on single phase flows with Rushton turbines (Section 2) shows that Reynolds Averaged Navier Stokes (RANS) simulations yield decent results for single-impeller geometries (Coroneo et al, 2011), but appear to consistently overestimate mixing times in multiimpeller geometries (Montante et al, 2005;Moštěk et al, 2005;Kukuková et al, 2005;Jahoda et al, 2007); this over-estimation may hold for other impeller types at large spacing (Montante et al, 2005). Large Eddy simulations (LES) appear to adequately capture mixing behavior, but the required computation time prohibits routine application.…”
Section: Introductionmentioning
confidence: 99%
“…For 2-PBT configurations, the MAT approach and the FTT both predict around 10% deviations from experimental data. Equation (1) with a ¼ 1:67 yields 47.0, a within 5% deviation to experiment for 2PBT C 2 ¼ 0:18; and 47.4 for 2PBT C 2 ¼ 0:23, which means an overestimation of 30%, this is expected since the accuracy of this equation has not been confirmed for configurations with large impeller spacing.…”
Section: Comparison and Evaluationmentioning
confidence: 87%
“…9 The second category of mixing performance studies involves experimental correlations. Rodgers et al 10 proposed Equation (1) as the correlation of 95% dimensionless mixing time N rps θ 95 for dishedbottom stirred tanks with a Cowles disc, a six-blade Rushton turbine, and a four-blade pitched-blade turbine. The N rps is impeller revolution per second, and α represents the ratio of the dished-base height to the tank diameter.…”
mentioning
confidence: 99%
See 1 more Smart Citation